PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS APLIKASI SWAY PADA PEMBELAJARAN IPAS DI KELAS IV SEKOLAH DASAR - Mhd. Ilham; Arwin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research is motivated by the results of observations found in elementary schools that there is no development of learning media based on the Sway application on IPAS in class IV. In the learning process, the learning media used by teachers tend to be pictures made of paper and pictures on display in the classroom. It is still rare to see teachers using technology-based learning media such as the use of the Sway application. The purpose of this research is to develop a valid and practical Sway application-based media. This research is a development research (R&D) with the ADDIE model which consists of five stages, namely analysis, design, development, implementation, and evaluation. Data collection used validation sheets and response questionnaires. The validation sheet consists of material validation sheet, language validation, and media validation. The response questionnaire consists of teacher and learner response questionnaires. The test subjects in this study were 27 students in class IV SDN 01 Bandar Buat, and 28 students in class IV SDN 20 Indarung. The results of the Sway application-based learning media development research developed have been validated as valid with an average validator assessment of 90.60%. Based on the results of the teacher and student response questionnaire at SDN 01 Bandar buat, it can be seen that the learning media is very practical to use with the results of the percentage of practicality of 91.67%, and 93.67%, and SDN 20 Indarung with a percentage of 95.83% and 95.54% with a very practical category